(3TQM OjhGf GdNfSGAs - (3GdNfSGA , JeGVQ HfJ YeQh Hf GdMGQK Hf GdTQjO,J (B24 (3g` s
(3ChdgG (B:s
(3eRL Ydi LfH GMOGf EPG ZOJ fcHGA JbWY KGHJ GdCWfGf s
(3BNQgG (B:s
(3hdjLYd aQSg hSdGeg ajeG jgeQfi bGd aNQL Gdjg CHhgG abGd EfgG SCdJ s
(3fSNI KGfjgs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B92s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B129 s
Keywords: (3GdCOHs